2006
DOI: 10.1111/j.0014-3820.2006.tb01179.x
|View full text |Cite
|
Sign up to set email alerts
|

Selection and Inbreeding Depression: Effects of Inbreeding Rate and Inbreeding Environment

Abstract: The magnitude of inbreeding depression in small populations may depend on the effectiveness with which natural selection purges deleterious recessive alleles from populations during inbreeding. The effectiveness of this purging process, however, may be influenced by the rate of inbreeding and the environment in which inbreeding occurs. Although some experimental studies have examined these factors individually, no study has examined their joint effect or potential interaction. In the present study, therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 113 publications
2
61
0
Order By: Relevance
“…Environmental conditions during inbreeding and when assessing fitness consequences of inbreeding rates are likely to have a large impact on the outcome (Bijlsma et al 1999;Day et al 2003;Swindell and Bouzat 2006b). Although the current study does not account for all issues mentioned above we do (1) investigate realistic levels of inbreeding, (2) test a large number of ecologically relevant traits and (3) study inbreeding depression under benign and stressful conditions (although only for two traits).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental conditions during inbreeding and when assessing fitness consequences of inbreeding rates are likely to have a large impact on the outcome (Bijlsma et al 1999;Day et al 2003;Swindell and Bouzat 2006b). Although the current study does not account for all issues mentioned above we do (1) investigate realistic levels of inbreeding, (2) test a large number of ecologically relevant traits and (3) study inbreeding depression under benign and stressful conditions (although only for two traits).…”
Section: Discussionmentioning
confidence: 99%
“…This slow rate will theoretically allow for selection to purge the deleterious alleles exposed by the increased homozygosity due to inbreeding (Kalinowski et al 2000;Swindell and Bouzat 2006a;Boakes et al 2007). Although some investigations have shown that purging can in fact contribute to the recovery from inbreeding depression in populations that have experienced an extensive decline in population size (Ehiobu et al 1989;Crnokrak and Barrett 2002;Reed et al 2003), other investigations reveal that this is not always the case (Ballou 1997;Pedersen et al 2005;Swindell and Bouzat 2006b;Boakes et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the prior inbreeding history and the inbreeding environment can have important consequences on the outcome of demographic bottlenecks, particularly in relation to their influence on the effectiveness of purging (Latta and Ritland 1994;Fowler and Whitlock 2002;Reed et al 2003a, b;Pedersen et al 2005;Swindell and Bouzat 2006c). For example, one can expect that different rates of inbreeding, i.e., how fast or slow inbreeding occurs, will enhance or decrease the purging of the populations' genetic load Day et al 2003;Swindell and Bouzat 2006c). We can assume that slower rates of inbreeding would enhance the effectiveness of selective purging.…”
Section: Bottlenecks As Unique Historical Eventsmentioning
confidence: 99%
“…Thus, a lack of interaction between fitness costs associated with low genetic variation and environmental stress may be caused by lack of additional deleterious alleles to be expressed in the populations with low genetic variation under stressful conditions. Swindell and Bouzat (2006) showed that Drosophila lines inbred under stressful environmental conditions expressed less inbreeding depression in the stressful environment in which they had evolved, as compared to lines inbred under benign conditions and later exposed to environmental stressor. Thus, if the toads have lost genetic variation under environmental conditions similar to those found in the outdoor treatment, the deleterious alleles expressed in that treatment may have been purged from the populations leaving them with a similar fitness level as the more genetically variable populations.…”
Section: Discussionmentioning
confidence: 99%
“…Since fragmentation of natural habitats is likely to result in higher environmental stress and increased loss of genetic diversity (Willi et al 2007), environment-dependent fitness costs associated with low genetic variation have considerable conservation implications. Moreover, if purging of deleterious alleles is important in reducing inbreeding depression under stressful conditions, the interaction between inbreeding depression and stress may be more detrimental in recently fragmented habitats where purging has not had the opportunity to act (Swindell and Bouzat 2006;Ficetola et al 2007). Clearly, more research on the role of interaction between inbreeding and environmental stress is needed in order to evaluate the consequences of habitat fragmentation and environmental stress on natural populations.…”
Section: Discussionmentioning
confidence: 99%